P350 CARDIOLOGY SPECIALISTS OPERATING IN THE VENETO REGION: AN ANALYSIS COVERING THE PERIOD BETWEEN 2013 AND 2019. (18th May 2022) - Zuin, M; Picariello, C; Rigatelli, G; Roncon, L; Bilato, C
Abstract: Background: The continuous aging of the population and the impact of cardiovascular diseases in terms of morbidity and mortality require a continuous and constant increase in health personnel throughout the country. The aim of the study is to evaluate the trend of cardiologist specialists available for the population living in the Veneto Region between 2013 and 2019. Materials and Methods: Data regarding the population living in Veneto region during the study period as well as the absolute number of cardiologists referred to 1000 inhabitants and the regional old–age index were extracted from the ISTAT portal (dati.istat.it) and then processed. The temporal variation in the number of cardiologist specialists operating in the Veneto region was evaluated with the Jonckheere–Terpstra test. Results: Between 2013 and 2019, the resident population in Veneto varied from 4, 926, 818 to 4, 879, 133 inhabitants. Cardiology specialists increased from 759 in 2013 to 869 in 2019; in particular, their availability, for every 1000 inhabitants, change from 0.15 to 0.18 with a total increase in the period considered of 0.4% (p for trend = 0.68), despite a continuous aging of the resident population, as evidenced by the old–age index (from 146.8 in 2013 to 173.1 in 2019, p = 0.01). The maximum increase in the number of specialists registered was 0.01 per 1000 inhabitants. (Figure 1 ). Conclusions: The availability of cardiology specialists in the Veneto Region, despite showing a slight positive althoug non significaqnt trend in recent years, continues to be lower than the care burden and the type of resident population, often elderly and with multiple comorbidities.